2015
DOI: 10.1063/1.4936630
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atomic structure on interface spin-polarization of half-metallic spin valves: Co2MnSi/Ag epitaxial interfaces

Abstract: Using density functional theory calculations motivated by aberration-corrected electron microscopy, we show how the atomic structure of a fully epitaxial Co2MnSi/Ag interfaces controls the local spin-polarization. The calculations show clear difference in spin-polarization at Fermi level between the two main types: bulk-like terminated Co/Ag and Mn-Si/Ag interfaces. Co/Ag interface spin-polarization switches sign from positive to negative, while in the case of Mn-Si/Ag, it is still positive but reduced. Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The change of the structure and chemistry at interfaces can significantly affect the spin-electronic structure locally14; for example the interface spin-polarisation can be reduced or reversed which leads to spin-scattering phenomena detrimental to the spin-injection efficiency into the semiconducting substrate. Hence determining the spin-polarisation at interfaces is important in designing optimal systems for applications.…”
Section: Resultsmentioning
confidence: 99%
“…The change of the structure and chemistry at interfaces can significantly affect the spin-electronic structure locally14; for example the interface spin-polarisation can be reduced or reversed which leads to spin-scattering phenomena detrimental to the spin-injection efficiency into the semiconducting substrate. Hence determining the spin-polarisation at interfaces is important in designing optimal systems for applications.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the half-metallic nature of Heusler alloys at the interface can be sensitive to the exact configuration of the interface atoms, and this can affect the performance of the device. For example, it is known that Co 2 MnSi (CMS) grown on a silver surface changes significantly depending on whether it terminates with a Co layer or a Mn/Si layer [35]. For the CFAS/semiconductor interface, germanium provides an extremely good lattice match with only a 0.2% mismatch, compared to around 4.5% for CFAS/Si.…”
Section: Cfas/n-ge Interfacementioning
confidence: 99%
“…the spatial extent of the diffusion can be limited to a very narrow interface region [16]. However, even for ideal half-metallic electrodes and atomically abrupt interfaces, DFT studies predict a reduction of the SP in the vicinity of the interface, as reported for Heusler/ GaAs and Heusler/Ag interfaces in [17][18][19]. In other words, structural and chemical abruptness of the interface does not necessarily lead to an interface electronic structure desirable for spintronic devices.…”
Section: Introductionmentioning
confidence: 99%